Heat dissipation analysis and multi-objective optimization of microchannel liquid cooled plate lithium battery pack. - Xueyong Pan; Chuntian Xu; Xuemei Sun; Jianhui Shi; Zhilong Zhou; Yunlong Liu (PLoS ONE)
An efficient battery pack-level thermal management system was crucial to ensuring the safe driving of electric vehicles. To address the challenges posed by insufficient heat dissipation in traditional liquid cooled plate battery packs and the associated high system energy consumption. This study proposes three distinct channel liquid cooling systems for square battery modules, and compares and analyzes their heat dissipation performance to ensure battery safety during high-rate discharge. The results demonstrated that the extruded multi-channel liquid cooled plate exhibits the highest heat dissipation efficiency. Subsequently, response surface experiments were conducted to analyze the width parameters of various flow channels in the liquid cooled plate Finally, the Design of Experiment (DOE) was employed to conduct optimal Latin hypercube sampling on the flow channel depth (H), mass flow (Q), and inlet and outlet diameter (d), combined with a genetic algorithm for multi-objective analysis. The Tmax of the battery module decreased by 6.84% from 40.94°C to 38.14°C and temperature mean square deviation decreased (TSD) by 62.13% from 1.69 to 0.64. Importantly, the battery thermal management model developed in this study successfully met heat dissipation requirements without significantly increasing pump energy consumption.